(untitled) (Web of Technology: Multidimensional Research Journal, 2026)
This article explores the possibilities and limitations of teaching Japanese using AI. It analyzes AI technologies, language learning applications, and interactive tools. At the same time, issues such as translation errors, contextual understanding limitations, and the necessity of real communication are discussed. In conclusion, while AI is an effective aid in language learning, it should be used with caution.